Comprehensive Evaluation of Anterior Corneal Change in Asphericity Calculated by the Tangential Radius of Curvature after LASIK. (6th February 2017) - Ying, Jinglu; Cai, Jianqiu; Zhu, Leru; Zha, Yi
Abstract : To evaluate the change in the anterior corneal asphericity (ΔQ ) comprehensively calculated using the tangential radius (r t ) after LASIK. Forty-two right eyes were evaluated using the Orbscan II corneal topographer. The pre- and postoperative Q -values of the flat principal semimeridians calculated by the sagittal radius were compared to those by the tangential radius. The Q -value of each semimeridian in the horizontal region was calculated by r t . Fourier fitting was used to model the 360-semimeridional variation of Q -values and to fit the Q -values in the vertical region before and after surgery. There were significant differences in Q -values between the two methods before (P < 0.001 ) and after surgery (P = 0.003 ). A significant increase in postoperative Q -value was detected compared to preoperative Q -value (P < 0.001 ) calculated by r t . The 360-semimeridional variation of the Q -values was well fitted with a third- and fourth-degree Fourier function before and after surgery. The ΔQ -value distribution presented double valley variation, with the amount of ΔQ being lowest in the near-vertical regions and highest in the near-horizontal regions. Calculating the Q -value with r t combined with Fourier fitting, we evaluated 360 ΔQ -values' variation of semimeridians of the entire anterior corneal surface and then displayed true and complete anterior corneal shape after LASIK.